Pengaruh Kualitas Produk, Harga, dan Promosi Terhadap Keputusan Pembelian pada Marketplace Lazada - Suryadi Suryadi; Aslam Mei Nur Widigdo (GREAT: Jurnal Manajemen dan Bisnis Islam, 2026)
This study aims to analyze the influence of product quality, price, and promotion on purchasing decisions on the Lazada marketplace. The research method used was a quantitative method with an associative approach. The data collection instrument used a questionnaire distributed online. The population in this study was Lazada marketplace users in Depok City, resulting in a sample of 100 respondents selected using the Lemeshow formula. The data analysis method used was Structural Equation Modeling (SEM) with SmartPLS software version 4.0. The results showed that product quality had a significant positive effect on purchasing decisions. Price had a negative but insignificant effect on purchasing decisions. Promotion had a positive but insignificant effect on purchasing decisions.